Students experience using learning factory at the Faculty of Industrial Management - Mohd Ghazali, Maarof; Muhammad Zam Zahari, Bohari (Universiti Malaysia Pahang, 2023)
One of the issues faced by the industry internationally is a lack of skilled workers to meet growing industrial demands. To satisfy the demanding requirements of the manufacturing industry in such a scenario, both the educational content and didactical methodologies need to be enhanced. However, the university and other higher education institutions do not currently use training and teaching strategies that prepare students for employment in the industrial sector. The learning factory concept can be introduced to the institution to resolve this problem. The learning factory technique mixes business activities with the educational process. This study evaluates the student’s perception in using the learning factory concepts at the Universiti Malaysia Pahang, a Malaysian public university located in Pahang, Malaysia. A qualitative research method was employed, and data was collected by interviewing six undergraduate students who had used the learning factory for their lean manufacturing subject. The interview took place at the end of the semester using a structured, open-ended interviewing questions technique. According to the study, the learning factory has four primary advantages which are increase students' interest in TVET topics, boost their level of soft skills, increase their comprehension, and offer tools to help them retain knowledge. The findings of this study can be used to provide new suggestions for lecturers, instructors, or higher education institution administration on how to make teaching students simpler and more engaging using learning factory concept. Future research should study the relationship between learning factory infrastructure, instructional approaches, with student performance.